Outcome and Clinical Characteristics of Nosocomial Infection in Adult Patients Undergoing Extracorporeal Membrane Oxygenation: A Systematic Review and Meta-Analysis - Li, Xiyuan; Wang, Liangshan; Wang, Hong; Hou, Xiaotong (Frontiers in Public Health, 2022)
Objective: This study conducts a meta-analysis of the clinical outcomes of nosocomial infection in adult patients receiving extracorporeal membrane oxygenation (ECMO) and systematically evaluates the clinical epidemiological characteristics. Methods: The adult patients included were treated with ECMO and were evaluated with inclusion and exclusion criteria. The retrieval strategies, the prevalence, the incidence, the mortality, ECMO use time, intensive care unit (ICU) stay time, hospital stay time, and the risk factors of nosocomial infection were systematically evaluated; subsequently, a meta-analysis of the impact of nosocomial infection on the risk of in-hospital mortality was conducted. Results: A total of 25 retrospective studies were included, and 19 studies were included in the meta-analysis. The prevalence of nosocomial infection was 8.8%–64%, the incidence was 1.7‰–85.41‰ (the number of days that the patient received ECMO), and the in-hospital mortality was 31.5%–75.4%. The duration of ECMO usage and the length of ICU stay were longer for infected patients. Compared with non-infected patients, the meta-analysis revealed that nosocomial infection increased the relative risk of death of the adult patients receiving ECMO by 32%. The risk factors tended to be the duration of ECMO usage and the disease severity score. Conclusion: Adult patients treated with ECMO have a high prevalence of nosocomial infection. In addition, their ICU and hospital stays are longer. Nosocomial infection significantly increases relative risk of in-hospital mortality.